2023
DOI: 10.1007/s10758-023-09700-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effectiveness of Flipped Classroom on STEM Student Achievement: A Meta-analysis

Jin Gong,
Sanfa Cai,
Ming Cheng

Abstract: A 'flipped classroom' creates a dynamic and effective learning environment where students learn basic knowledge at home and engage in active learning activities during the class. It has been widely used across different STEM (Science, Technology, Environment, Mathematics) disciplines. However, there is a lack of systematic and quantitative assessments of the effectiveness of the flipped classroom model on student performance. In this study, a meta-analysis was conducted with 53 research articles on the flipped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 91 publications
0
1
0
Order By: Relevance
“…There could be added benefits to adding such a framework. For example, the DAL approach has synergies with a flipped classroom pedagogy by emphasizing smaller class sizes and enhanced collaboration, key factors for the flipped model’s success. In DAL, the shift to smaller, flexible learning spaces led by TAs facilitates active, collaborative in-class activities. Such an approach facilitates personalized feedback and peer-to-peer engagement, which are central in flipped classrooms where preclass content acquisition is applied during class time.…”
Section: Discussionmentioning
confidence: 99%
“…There could be added benefits to adding such a framework. For example, the DAL approach has synergies with a flipped classroom pedagogy by emphasizing smaller class sizes and enhanced collaboration, key factors for the flipped model’s success. In DAL, the shift to smaller, flexible learning spaces led by TAs facilitates active, collaborative in-class activities. Such an approach facilitates personalized feedback and peer-to-peer engagement, which are central in flipped classrooms where preclass content acquisition is applied during class time.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that textbook readings or video lectures can promote learning gains [18,19], though one study that compared different formats for preclass activities found that video lectures had an advantage over textbook readings [19]. More importantly, studies have shown that students' active engagement in preclass activities is critical to student learning [12,13,16,17]. This is consistent with the ICAP Framework-Interactive, Constructive, Active, and Passive-which predicts that as students become more engaged with learning materials, their learning will increase [20].…”
Section: Effective Preclass Activitiesmentioning
confidence: 99%
“…Indeed, studies of flipped models that use video lectures with no methods for assuring students are actively engaged with the materials show small or no student gains [12,13,16]. The ability to embed required questions within a video can help to support student selfassessment and provide accountability for the completion of preclass activities, which may explain why students completing such activities were found to significantly outperform students completing textbook readings [21].…”
Section: Effective Preclass Activitiesmentioning
confidence: 99%
See 1 more Smart Citation